Ценностное значение интерактивных методов обучения - Остапенко, Л.Г. (My University, 2016)
This article considers the features of interactive learning , the requirements and principles of interactive learning . Recommendations on the use of active learning methods and their effectiveness .
Keywords: interactive learning; active learning methods; conditions for the use of interactive teaching methods; the principles of interactive learning; creative tasks